Modification of Screen Printed Carbon Electrode (SPCE) with Fe3O4 for the Determination of Nitrite (NO2-) in Squarewave Voltammetry - Erica Marista Rosida; Ani Mulyasuryani; Rachmat Triandi Tjahjanto (Universitas Jenderal Soedirman, 2017)
Nitrite is one of the food preservatives that the government permits, but on the use of over limits can cause endanger health, so it is necessary to control the content of nitrite in the food. Modification of electrodes on a screen printed carbon electrode (SPCE) with Fe3O4 has been successfully done for determination of nitrite. Modification of the electrode has been done by electrodeposition with cyclic voltammetry. Electrodeposition successfully performed with an electrolyte solution of FeCl3 in ethanol. Selection of the optimum drying temperature modified electrode obtained based on the respond of the solution of nitrite in Britton Robinson buffer pH 8. The result of the modification electrode used for the determination of nitrite with squarewave voltammetry method. Reaction between Fe3+ with nitrite a basis for determining nitric indirectly measured so that the peak current is the peak current of Fe3+ of about 0,55 V vs Ag/AgCl. The results showed nitrite measurements with this method has a detection limit of 1.3 x 10-8 M.